Pentingnya Meningkatkan Kompetensi Pedagogik Guru Kristen dalam Proses Pembelajaran: Suatu Kajian Filosofi Kristen [The Importance of Improving the Pedagogical Competence of Christian Teachers in the Learning Process: a Study of Christian Philosophy] - Sumbayak, Yesika; Suparman, Suparman (Universitas Pelita Harapan, 2023)
Christian education is a God-centred education, having a transformative and holistic purpose to reconcile students who have fallen into sin and restore the image of God in students. Teachers as transformative and holistic agents need to have the right perspective on students. The teacher's perspective on students will affect the pedagogical competence of the teacher. A good pedagogical competence can create meaningful learning. However, in reality, secular philosophy has influenced teachers in achieving educational purpose as well as the way teachers view students. Secular education makes the teacher as the centre of education and views the students as machines or robots that receive knowledge according to what the teacher delivers. The purpose of this study is to examine the importance of pedagogical competence of teachers in Christian philosophy. This study uses a literature review method by researching several theories and journals. The results showed that it is important for Christian teachers as co-workers of God to develop pedagogical competence. Through this competence, it will help Christian teachers in applying learning methods that are able to transform students to be more like Christ. In conclusion, the basic thing that teachers need to have is awareness and humility to continuously learn and develop every ability they have as a form of accountability before God. BAHASA INDONESIA ABSTRACT: Pendidikan Kristen adalah pendidikan yang berpusat pada Tuhan, yang memiliki tujuan transformatif dan holistik untuk mendamaikan siswa yang telah jatuh ke dalam dosa dan memulihkan gambar Allah dalam diri siswa. Guru sebagai agen transformatif dan holistik perlu memiliki cara pandang yang tepat terhadap siswa. Cara pandang guru terhadap siswa akan mempengaruhi kompetensi pedagogis yang dimiliki oleh guru. Kompetensi pedagogis yang baik dapat menciptakan pembelajaran yang bermakna. Namun pada kenyataannya, filosofi sekuler telah mempengaruhi guru dalam mencapai tujuan pendidikan dan juga cara pandang guru terhadap siswa. Pendidikan sekuler menjadikan guru sebagai pusat pendidikan dan memandang siswa sebagai mesin atau robot yang menerima pengetahuan sesuai dengan apa yang disampaikan oleh guru. Tujuan dari penelitian ini adalah untuk melihat pentingnya kompetensi pedagogis guru dalam filsafat Kristen. Penelitian ini menggunakan metode tinjauan literatur dengan menelaah beberapa teori dan jurnal. Hasil penelitian menunjukkan bahwa penting bagi guru Kristen sebagai rekan sekerja Tuhan untuk mengembangkan kompetensi pedagogis. Melalui kompetensi ini, akan menolong guru Kristen dalam menerapkan metode pembelajaran yang mampu mentransformasi siswa menjadi semakin serupa dengan Kristus. Kesimpulannya, hal mendasar yang perlu dimiliki oleh para guru adalah kesadaran dan kerendahan hati untuk terus belajar dan mengembangkan setiap kemampuan yang dimilikinya sebagai bentuk pertanggungjawaban di hadapan Tuhan.